(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2024)
Background. The research aimed to find a convenient preparative method for the synthesis of tantalum water-soluble complexes from metal oxide, which would not require harsh or hazardous reaction conditions or the use of expensive, less accessible reagents. The application of the triethylamine-hydrogen fluoride complex as an inexpensive and safe surrogate for hydrofluoric acid facilitated the conversion of tantalum oxide into a form suitable for further transformations in aqueous or organic environments under mild conditions and without any restrictions on the use of glassware. Methods. In this work, a method for dissolution of tantalum pentaoxide, a relatively chemically inert compound, with formation of highly soluble fluoride complex was developed. The variety of techniques were used to identify the complex, such as: IR, UV/Vis and NMR spectroscopy. All materials were of analytical grade and obtained from commercial sources without further purification. The IR spectra of the synthesized compounds were recorded on a Fourier IR spectrometer Perkin-Elmer ВХ (400-4000 cm-1) in KBr tablets. Electron spectra of diffuse reflection (ESD) of polycrystalline of samples in the UV and visible range were recorded on a Varian spectrometer 5000. The intensity was measured relative to MgO or KBr. The solvents were purified according to the standard procedures. All other starting materials were purchased from commercial sources. 1H and 19F NMR spectra were recorded on a Varian Gemini 2000 spectrometer. Results. It was found that old samples of tantalum oxide, inert to most inorganic and organic acids and bases, are easily converted to fluorotantalates by reacting with commercial trimethylamine hydrofluoric acid complex at room temperature within short reaction times. The reaction is easily scaled up to multigram quantities and the product (NHEt3)2[TaF7] is obtained in essentially pure form after operationally simple workup protocol. Bench stable tantalum complex is insensitive to air and moisture. Conclusions. A developed protocol can serve as a convenient and safe starting point for the preparation diverse coordination and organometallic tantalum compounds both by fluoride ligand substitution and organic cation exchange. Tantalum oxide hydrofluoride-dissolution – precipitation-by-hydrolysis cycle may also be used for crude tantalum sample purification owing to the crystalline nature of the heptafluoride complex and its other physico-chemical properties.